Association of patella alta with worsening of patellofemoral osteoarthritis-related structural damage: data from the Osteoarthritis Initiative. Issue 2 (February 2019) - Haj-Mirzaian, A.; Guermazi, A.; Pishgar, F.; Pourvaziri, A.; Roemer, F.W.; Sereni, C.; Hakky, M.; Zikria, B.; Stefanik, J.J.; Demehri, S.
Summary: Objectives: To determine the association between Insall-Salvati ratio (ISR), a measure of patella alta, and worsening of Magnetic Resonance Imaging (MRI)-based osteoarthritis (OA)-related patellofemoral joint structural damages over 24-month in participants of the Osteoarthritis Initiative (OAI). Design: Using weighted random sampling method, we selected a sample of 500 knees (from 1, 677 knees with available baseline and 24-months MRI OA Knee Score (MOAKS) measurements), which is OAI-representative regarding knee OA-related factors (i.e., baseline age, sex, body mass index (BMI), and radiographic Kellgren–Lawrence grading). The ISR was measured in all enrolled knees using baseline sagittal 3T-MRI plane by three radiologists. Baseline and 24-month MOAKS variables for patellofemoral bone marrow lesions (BMLs), cartilage damages, and osteophytes were extracted, and the associations between ISR and 24-month worsening of these 3T-MRI features were evaluated using multivariable regression models. After computing receiver operating characteristic curves, the optimal cutoff point of ISR for indicating worsening of patellofemoral OA was determined. P -values were adjusted for multiple comparisons and false discovery rate (FDR) adjusted P -values were reported. Results: In this longitudinal analysis, 24-month worsening of BML (odds ratio [OR] (95% confidence interval [95% CI]):11.18 (3.35–39.6), adjusted-p-value:<0.001) and cartilage scores (OR:7.39 (1.62–34.71), adjusted-p-value:0.042) in lateral patella was associated with higher baseline ISR. However, higher ISR was not statistically associated with medial patellar or medial and lateral trochlear BML or cartilage scores worsening. We determined the optimal cutoff point of ISR≥1.14 (95% CI: 1.083–1.284) for predicting lateral patellofemoral OA-related structural damages worsening over 24-months (sensitivity:73.73%; specificity: 66.67%). Conclusions: Given the uncertainly surrounding the results, our overall findings suggest that ISR could be considered as a predictor of lateral patellofemoral OA-related structural damages worsening with the optimal cutoff point of ≥1.14 using knee sagittal MRI measurements.